2022
DOI: 10.3390/jdb10010006
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Cells Isolated from Human Femoral Heads into Functional Osteoclasts

Abstract: Proper formation of the skeleton during development is crucial for the mobility of humans and the maintenance of essential organs. The production of bone is regulated by osteoblasts and osteoclasts. An imbalance of these cells can lead to a decrease in bone mineral density, which leads to fractures. While many studies are emerging to understand the role of osteoblasts, less studies are present about the role of osteoclasts. This present study utilized bone marrow cells isolated directly from the bone marrow of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…Another critical factor is the concentration of the two cytokines that reprogram monocytes towards osteoclasts, M-CSF and RANKL. Confirming previously published data, our results demonstrate that high concentrations of these two factors are clearly superior in inducing efficient osteoclast differentiation [ 26 , 28 30 ]. Some studies have applied an even higher concentration of RANKL (100 ng/ml) and observed a further increase in the number of TRAP-positive cells.…”
Section: Discussionsupporting
confidence: 91%
“…Another critical factor is the concentration of the two cytokines that reprogram monocytes towards osteoclasts, M-CSF and RANKL. Confirming previously published data, our results demonstrate that high concentrations of these two factors are clearly superior in inducing efficient osteoclast differentiation [ 26 , 28 30 ]. Some studies have applied an even higher concentration of RANKL (100 ng/ml) and observed a further increase in the number of TRAP-positive cells.…”
Section: Discussionsupporting
confidence: 91%
“…The activation of osteogenic signaling pathways in osteoblasts is mediated by BMP-2, which was approved by the FDA in 2002 to be used as a therapeutic [84]. However, several side-effects were reported after usage of BMP-2, such as hematoma formation, radiculitis, and increased osteolysis, as BMP-2 also enhances osteoclastogenesis [67,68,85,86]. Further, it was demonstrated that primary osteoblasts isolated from OP patients and BMSCs obtained from aged (15-and 20-month) B6 mice are unresponsive to BMP-2 stimulation [58,67].…”
Section: Discussionmentioning
confidence: 99%
“…As the bone tissue is obtained from donors aged above 60y, the bone is likely to contain yellow marrow, rich in adipocytes and with reduced hematopoietic activity, but the marrow content was not specifically characterized in the explants [55]- [57]. On the other hand, previous research demonstrated that bone marrow cells isolated from human femoral heads of osteoarthritic patients were able to differentiate into viable and functional osteoclasts in vitro [58]. It was found that only optimal culture conditions, 25 ng/ml M-CSF for 3 days followed by 50 ng/ml RANKL and 25 ng/ml M-CSF for 11 days, generated large amounts of osteoclasts [58].…”
Section: Discussionmentioning
confidence: 99%